Higher Sensitivity Provided by the Combination of Two Lateral Flow Immunoassay Tests for the Detection of COVID-19 Immunoglobulins - Daoud, Ziad; McLeod, Jesse; Stockman, David L. (Frontiers in Cellular and Infection Microbiology, 2020)
SARS-Cov-2 was identified in Wuhan, China in December 2019. The World Health Organization (WHO) declared it a pandemic in March of 2020. COVID-19 has now been reported on every continent. In the United States, the total number of confirmed reported cases of COVID-19 has exceeded 1.8 million with the total death exceeding 100,000 people. The most common investigational diagnostics of this disease are RT-PCR and serology testing. The objective of this work was to validate two commercial kits for the detection of IgM and IgG using lateral flow immunoassay tests and to study the effect of the combination of both serology kits for better detection of immunoglobulins. A total of 195 patients presenting with respiratory symptoms suggestive of infection with SARS-Cov-2 were subject to serology and molecular testing. Two lateral flow immunochromatographic assay kits were used: the Healgen Scientific for SARS-CoV-2 IgM/IgG and the Raybiotech for SARS-CoV-2 IgM/IgG. Sensitivity and specificity of each kit alone and in combination were determined and compared. The limit of detection, inter and intra test variations, as well interfering substances and cross reactivity were also studied for both kits. The results show sensitivities for IgM detection varying between 58.9 and 66.2% for the kits alone and 87.7% of the combination of both kits. IgG detection was not significantly affected by this combination. Both kits manifested high specificities (99.2–100%). Both kits showed high clinical performance in terms of cross reactivity and interfering substances. Our results suggest using combinatory testing for the serology of COVID-19 after a full evaluation study, assessing all the parameters affecting their clinical performance before deciding on this combination.